PLÁNOVANIE VYBRANÝCH MANIPULAČNÝCH OPERÁCIÍ PRI ZABEZPEČENÍ EVAKUÁCIE MATERIÁLU (Perner's Contacts, 2007)
The paper presents the tasks, which bear on evacuation of material in extreme or crisis situation. The paper deals also with some factors and conditions of evac material handling and with calculation of means of mechanization and chosen basic indicators.
Keywords: security; evacuation; material handling; manipulation; material